The weeping heart, the choked lung, the blinded eye, and the crying femur: A saga of juvenile dermatomyositis - Arun Hegde; Suchi Acharya; Subramanian Shankar; Abhishek Kumar; Uday Bhanu Kovilapu (Indian Journal of Rheumatology)
Juvenile dermatomyositis (JDM) is the most common inflammatory myositis in children that primarily involves the skeletal muscles and skin. However, it can manifest with a diverse range of clinical features across multiple organ systems. JDM vasculopathy causing optic neuritis and medullary bone infarcts in children are rare manifestations of JDM and have been seldom reported in literature. Similarly, cardiovascular manifestations in the form of refractory myocarditis leading to congestive cardiac failure during the early course of the disease have also been rare findings. Early diagnosis and aggressive management of such complications using biological disease-modifying synthetic antirheumatic drugs has significantly reduced the mortality and morbidity associated with JDM. Herein, we report a mini case series of three patients with JDM who presented with these rare systemic manifestations and achieved favorable outcomes while being managed using the Childhood Arthritis and Research Alliance-Treatment Protocols.